1993
DOI: 10.1007/bf01309748
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biological differentiation of dengue 3 isolates obtained from clinical cases in Java, Indonesia, 1976?1978

Abstract: Previous epidemiological, virological and clinical studies have documented a series of outbreaks of dengue fever and dengue haemorrhagic fever/dengue shock syndrome which occurred in Java, Indonesia in 1976-1978. In the current study we compare growth characteristics in cell culture, and nucleotide sequence data for the viral prM and E genes, of five low passage DEN-3 isolates obtained during these epidemics from clinically defined cases. All isolates had the same passage history: human sera were passed twice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
2
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
4
2
0
Order By: Relevance
“…The AA substitutions were shared by isolates causing both DF and DHF (Fig 6). Previous studies have also observed similar findings and have found no reproducible genetic differences related to disease severity [6972]. However, we are aware that only E protein AA sequences were compared in this study.…”
Section: Discussionsupporting
confidence: 81%
“…The AA substitutions were shared by isolates causing both DF and DHF (Fig 6). Previous studies have also observed similar findings and have found no reproducible genetic differences related to disease severity [6972]. However, we are aware that only E protein AA sequences were compared in this study.…”
Section: Discussionsupporting
confidence: 81%
“…This pic ture concurs with the data of other workers who studied other dengue 3 viral genes [16][17][18]. 256 Chow/Seah/Chan NS3 Sequences of Dengue 3 Virus Strains Interestingly, the strains from Malaysia and Singapore isolated in the more recent outbreaks of the late 1980s and early 1990s were more closely related to the Thai cluster, implying their evolution from the latter.…”
Section: Discussionsupporting
confidence: 80%
“…The correlation of some of our findings derived from the more 'stable' NS3 gene compared with those of work ers elsewhere who studied other relatively more 'variable' dengue 3 virus genes such as the envelope, premembrane and membrane sequences [16][17][18] verify the validity of our data. In addition, the useful interpretation of new evo lutionary and/or epidemiologic links exhibits the feasibili ty of exploiting NS3 base differences between strains for constructing informative phylogenetic trees.…”
Section: Discussionsupporting
confidence: 67%
“…1999; Holmes & Burch 2000). Differences among dengue of the same type within the same geographical region was previously reported by Lee et al . (1993), Attatippaholkun et al .…”
Section: Discussionsupporting
confidence: 77%